Take CGIAR and Partners’ Ag-innovations to the Farmer: Building Livelihoods and Resilience of Smallholders under a Changing Climate in Ethiopia - Makonnen, Brook T.; Belay, Berhanu (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Ethiopian government has recently convened a national conference on ‘Shaping Agriculture for Greater Impact’ to map the path forward in a renewed commitment towards agricultural transformation through resilient agriculture and food systems. These include forging innovative partnerships, public policy, food value chain and livelihood, and on-farm and productive landscape solutions. This gathering is part of the high-level conference series co-hosted by Ethiopia’s Ministry of Agriculture and Ethiopia’s Agricultural Transformation Institute in collaboration with AICCRA-Ethiopia, hosted at the International Livestock Research Institute (ILRI), and expected to accelerate the integration of CGIAR and its national and international partners - to improve livelihoods and build agri-food system resilience and adaptive capacity to changing climate: (i) Through sharing of science, knowledge, and innovations and climate-informed digital agriculture data hubs and decision support to address critical gaps in climate information services CIS), NextGen seasonal and sub seasonal forecasts, early warning systems (EWS) for early action (EA) and climate smart agriculture (CSA) technologies and provisions, and to promote large-scale core-country and cross-border/regional adoption including via S-S learnings, (ii) Build capacity/multi-actor partnerships for delivery – education-research-extension continuum - to anticipate climate risks, enhance preparedness and accelerate prioritization, user-centric bundling and uptake of best-bet resilience building and adaptive measures, and (iii) Contextualize CIS, EWS/EA, climate-informed digital ag-advisories, CSA link bundled packages to transfer systems for scaling, and improve beneficiaries and end-users’ access to CIS and ag-advisories for decision making. The conference titled, ‘Take CGIAR and Partners Ag-innovations to the Farmer’ - Building Livelihoods and Resilience of Smallholders under a Changing Climate in Ethiopia was organized as a follow-up of the Shaping Agriculture for Greater Impact in Ethiopia Workshop Series and was a collaborative effort between the Ministry of Agriculture of Ethiopia, the Ethiopian Agricultural Transformation Institute (ATI), and the International Livestock Research Institute’s AICCRA project. Over 100 participants from federal ministries, national research institutes, academia, private sector, development sector, international research institutes, funding agencies and diplomatic communities gathered on May 25, 2023, at Radisson Blu Hotel, Addis Ababa.